Giordano Brunos konzeption des schönen in "De gli eroici furori" - Kornmeier, Bárbara (Estudios Humanísticos. Filología, 1995)
The main of this paper is to examine Giordano Bruno's conception of beauty his book De gli Eroici Furori. Firstly, I place Bruno's conception of beauty in the frame of his theory of knowledge, whose central problem is how we can know the divinity. Next, I connect Bruno's analysis of beauty with 'the problem of form and harmony, which is traced back to the classical problemof unity in variety. On this basis I examine the question about how we can know the beauty in the world. The knowledge of beauty requires that the beauty in the world is given a spiritual form, the unity of the idea, i.e. it requires the acknowledgement of its divine origin.